Diagnosis of the attitudes towards ICT of education students according to gender and educational modality - Francisco David Guillén-Gámez; Sonia Janeth Romero Martínez; Xavier Giovanni Ordóñez Camacho (Universidad de Guadalajara, 2020)
Attitudes towards technology are ideas, conceptions and thoughts that guide actions and, in the case of students, can influence the learning process and academic performance. The aim of this research is to know if there are significant differences between face-to-face and completely distance learning students in relation to their attitude towards technology and according to gender. To meet this objective a non-experimental mixed research was carried out with a sample of 180 Early Childhood and Elementary Education students. Attitudes were measured and scores were compared using both parametric and non-parametric statistics. Following this methodology, the study found statistically significant differences in the average attitude towards technology depending on the educational modality and gender; specifically, men and distance learning students show more favorable attitudes in the affective dimension while face-to-face students exhibit more favorable scores in cognitive and behavioral attitudes. The conclusions derived from this study may help to develop educational interventions focused in the improvement of unfavorable attitudes.